Alveolar‐filling growth pattern of sarcomatoid malignant pleural mesothelioma. Issue 5 (4th July 2016) - Hayakawa, Takamitsu; Tajima, Shogo; Takanashi, Yusuke; Takahashi, Tsuyoshi; Neyatani, Hiroshi; Funai, Kazuhito
Abstract : A case of sarcomatoid malignant pleural mesothelioma showing extremely rare growth pattern is described. A 63‐year‐old man presented to our hospital with left pleural effusion. A computed tomography (CT) scan of the chest showed diffusely thickened left visceral and parietal pleura associated with intermingled pulmonary infiltrative shadowing. Biopsy of the pleura under general anaesthesia confirmed the diagnosis of sarcomatoid malignant pleural mesothelioma. The patient underwent left extra‐pleural pneumonectomy. Histopathologically, the sarcomatoid spindle tumour cells changed their morphology to polygonal cells in the pulmonary parenchyma and grew upwards, filling the alveolar space without the destruction of its septa, showing an alveolar‐filling growth pattern. The current report indicates a case of sarcomatoid pleural mesothelioma that shows an alveolar‐filling growth pattern, despite having not been thoroughly categorized in the World Health Organization (WHO) classification. Abstract : We present a case of sarcomatoid malignant pleural mesothelioma showing an extremely rare alveolar‐filling growth pattern, in which the tumour cells invaded the pulmonary parenchyma and proliferated to fill the alveolar space, without destroying the preexisting elastic framework of the alveolar septa.